The Role of Tourism in the Environmental Development of Mifala and Qanawat Villages – Suwayda Governorate (Damascus University Journal of arts and humanities sciences, 2021)
Mifala and Qanawat Villages enjoy many natural and cultural elements that give them both environmental and tourist significance. However, the region is threatened by environmental degradation and local population’s lack of sense of responsibility towards the environment.The activation of ecotourism in the villages of Mifala and Qanawat, and controlling local population’s use of the environment would help protect the environment and revive it in economic terms. These activities could include environment-friendly tourism, creating developmental work opportunities to improve the living conditions, and raising the environmental awareness of the inhabitants of the research area. That could be achieved by taking necessary measures to plan environmental tourism as one of the factors of environment preservation and development.
Keywords: The Role of Tourism in the Environmental Development of Mifala and Qanawat Villages – Suwayda Governorate